Andersonville [videorecording (DVD)] - Frankenheimer, John, 1930-2002; Emick, Jarrod; Forrest, Frederic; Marcoux, Ted; De Young, Cliff (Turner Home Entertainment : Warner Home Video, 2003)
The Civil War explodes, air thick with musket fire, soil drenched with the blood of kinsmen, bodies piling up like cords of wood. In the madness and fury, a small group of Union soldiers fall into the hands of the Confederate army. Overnight, they find themselves herded aboard a prison train bound for the deepest regions of the South, to a slice of Hell carved out of the Georgia clay known as Andersonville. A moving drama that tells the most tragic tales ever to come out of the Civil War.